2019
DOI: 10.13057/ijap.v9i01.33262
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Suhu Annealing terhadap Struktur Mikro dan Sifat Optik Lapisan Bismuth Ferrite (BiFeO3)

Abstract: This study aims to determine the effect of annealing temperature on the microstructure and optical properties of Bismuth Ferrite (BiFeO3) layers. BiFeO3 film was successfully deposited on a quartz substrate using the Chemical Solution Deposition (CSD) method. The microstructure was characterized by XRD and optical properties was characterized with UV-Vis spectrophotometer. The annealing temperature variations are 550 o C, 600 o C, and 650 o C. Annealing temperature affect the microstructure i.e., crystallite s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Moreover, there have been many studies that reported the Nd-doped BFO films deposited on (111) Pt/Ti/SiO2/Si [10], and transparent FTO [8,11], ITO [13], SRO [3], LAO [17] substrates. Also, among the available methods, thin film manufactured by a chemical solution deposition (CSD) or solgel method [18][19][20][21] has potential advantages, which are easy operation, low cost, high purity, and low heating temperature. However, few works have concerned Nd-doped BFO thin films with various doping levels depositing on transparent quartz substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there have been many studies that reported the Nd-doped BFO films deposited on (111) Pt/Ti/SiO2/Si [10], and transparent FTO [8,11], ITO [13], SRO [3], LAO [17] substrates. Also, among the available methods, thin film manufactured by a chemical solution deposition (CSD) or solgel method [18][19][20][21] has potential advantages, which are easy operation, low cost, high purity, and low heating temperature. However, few works have concerned Nd-doped BFO thin films with various doping levels depositing on transparent quartz substrates.…”
Section: Introductionmentioning
confidence: 99%